On the relations between kinetic energy and linear momentum, angular momentum of the particle and of the rigid body - Khang, Nguyen Van (Vietnam Journal of Mechanics, 2001)
Using the definition for the partial derivative of a scalar in respect to the vector, this paper presents the relations between kinetic energy and linear momentum, angular momentum of the particle and of the rigid body. The obtained results are useful for the investigation of the dynamics of multibody systems